Comparison of three ways to determine and deliver pressure during nasal CPAP therapy for obstructive sleep apnoea. - West, S; Jones, DR; Stradling, JR (2006)
BACKGROUND: The simplest method of initiating and maintaining therapeutic continuous positive airways pressure (CPAP) therapy for obstructive sleep apnoea (OSA) has not been established. METHODS: Ninety eight subjects with OSA requiring CPAP treatment (more than 10 dips in oxygen desaturation of >4% per hour of sleep study and Epworth Sleepiness Score (ESS) >9) were randomised prospectively to three different methods of CPAP delivery for 6 months: (1) autotitration pressure throughout; (2) autotitration pressure for 1 week followed by fixed pressure (95th centile) thereafter; and (3) fixed pressure determined by algorithm (based on neck size and dip rate). Patients and investigators were blind to group allocation. One week after initiation the patients were routinely reviewed by sleep nurses. Study assessments took place before starting CPAP treatment and 1 and 6 months after to assess ESS, maintenance of wakefulness test, 24 hour blood pressure, general health (SF-36), and sleep apnoea related quality of life. CPAP internal monitoring data were also collected. RESULTS: There were no significant differences in any of the outcome measures or CPAP monitoring data between the three groups. The 95th centile CPAP pressures delivered in the 6 month and 1 week autotitration groups were higher than in the algorithm group, but the median pressures were lowest in the 6 month autotitration group. CONCLUSIONS: The method of determining CPAP pressure for treatment of moderate to severe OSA makes no significant difference to clinical outcome measures. The autotitration CPAP machine used has no advantage in this setting over simpler methods of pressure determination.